How to Manage High-Stakes Conflict. - Negotiation Institute, American; Christian, Kwame (linkedin.com, 2021)
In this course, adapted from the Negotiate Anything podcast, Yvette McGee Brown, a former Ohio Supreme Court Justice, discusses how to approach conflict.